Management of disease in nurses with varicose veins - Bingelytė, Greta; Paulikienė, Simona (Slauga. Mokslas ir praktika, 2022)
In 2020, one of the main causes in Lithuania was circulatory system diseases [1]. One common disorder of the vascular system is varicose veins. There are no exact statistics on the number of patients with varicose veins in Lithuania. Varicose veins are a venous disease that affects about 30 percent of the world’s population [2]. This article examines the disease management of nurses with varicose veins in the legs. The study included infection in 10 nurses diagnosed with varicose veins in the legs. The study identified genetic predisposition, posture, and physical work and overweight as the main risk factors for leg venous varicose veins. All informants use compression therapy, but only a few perform it on a regular basis. Nurses must also be physically active and follow dietary recommendations that use ointments to improve blood circulation in the legs. Due to the absence of pronounced varicose veins in the legs and the discourse caused by preventive measures, the investigator does not apply preventive measures. The reasons for the application of preventive measures are the information provided by specialists and colleagues. Further progression of the disease is a possible reason for the use of preventive measures.